Die Design of Flexible Multi-Point Forming Process - Abaas, Tahseen Fadhel; Younis, Karem Mohsen; Mansor, Khalida kadhim (Al-Khwarizmi Engineering Journal, 2019)
Multi-point forming (MPF) is an advanced flexible manufacture technology, and the technology results from the idea that the whole die is separated into small punches that can be adjusted height. This idea is applied to the traditional rigid blank-holder, so flexible blank-holder (FBH) idea can be obtained. In this work, the performance of a multi-point die is investigated with pins in square matrix and suitable blank holder. Each pin in the punch holder can be a significant moved according to the die high and at different load that applied with spring with respect to spring stiffness. The results shows the reduction in setting time with respect to traditional single point incremental forming process that lead to (90%). and also show during the forming process, the deformation of the interpolator can induce a shape error in the formed work-piece and the blank holder can reduce/eliminate dimples that sometimes arise in the work-piece. The minimum force applied using multi-point die is 28.556KN, while the load when complete the forming process is 30.8KN that caused displacement of die to 32.8mm.